Passive samplers to quantify micropollutants in sewer overflows: accumulation behaviour and field validation for short pollution events. (1st September 2019) - Mutzner, Lena; Vermeirssen, Etiënne L.M.; Mangold, Simon; Maurer, Max; Scheidegger, Andreas; Singer, Heinz; Booij, Kees; Ort, Christoph
Abstract: Contaminants in sewer overflows can contribute to exceedances of environmental quality standards, thus the quantification of contaminants during rainfall events is of relevance. However, monitoring is challenged by i) high spatiotemporal variability of contaminants in events of hard-to-predict durations, and ii) a large number of remote sites, which would imply enormous efforts with traditional sampling equipment. Therefore, we evaluate the applicability of passive samplers (Empore styrene-divinylbenzene reverse phase sulfonated (SDB-RPS)) to monitor a set of 13 polar organic contaminants. We present calibration experiments at high temporal resolution to assess the rate limiting accumulation mechanisms for short events (<36 h), report parameters for typical sewer conditions and compare passive samplers with composite water samples in a field study (three locations, total 10 events). With sampling rates of 0.35–3.5 L/d for 1 h reference time, our calibration results indicate a high sensitivity of passive samplers to sample short, highly variable sewer overflows. The contaminant uptake kinetic shows a fast initial accumulation, which is not well represented with the typical first-order model. Our results indicate that mass transfer to passive samplers is either controlled by the water boundary layer and the sorbent, or by the sorbent alone. Overall, passive sampler concentration estimates are within a factor 0.4 to 3.1 in comparison to composite water samples in the field study. We conclude that passive samplers are a promising approach to monitor a large number of discharge sites although it cannot replace traditional stormwater quality sampling in some cases (e.g. exact load estimates, high temporal resolution). Passive samplers facilitate identifying and prioritizing locations that may require more detailed investigations. Graphical abstract: Image 1 Highlights: Sampler accumulation behaviour and parameters quantified for short pollution events. Accumulation for short exposure dominated by sorbent or multi-step mechanism. Fast initial uptake lead to detection of all contaminants after 5min. Time-weighted water concentration higher with passive samplers in field study. Passive samplers suitable to screen for locations with (un)critical concentrations.